The Role of the Adipokine Leptin in Immune Cell Function in Health and Disease - Kiernan, Kaitlin; MacIver, Nancie J. (Frontiers in Immunology, 2021)
Leptin is a critical mediator of the immune response to changes in overall nutrition. Leptin is produced by adipocytes in proportion to adipose tissue mass and is therefore increased in obesity. Despite having a well-described role in regulating systemic metabolism and appetite, leptin displays pleiotropic actions, and it is now clear that leptin has a key role in influencing immune cell function. Indeed, many immune cells have been shown to respond to leptin directly via the leptin receptor, resulting in a largely pro-inflammatory phenotype. Understanding the role of adipose-tissue derived mediators in inflammation is critical to determining the pathophysiology of multiple obesity-associated diseases, such as type 2 diabetes, autoimmune disease, and infection. This review, therefore, focuses on the latest data regarding the role of leptin in modulating inflammation.